Characterization of APOE and TOMM40 allele frequencies in the Japanese population. Issue 4 (6th September 2017) - Nishimura, Akira; Nonomura, Hidenori; Tanaka, Shingo; Yoshida, Michihiro; Maruyama, Yuka; Aritomi, Yutaka; Saunders, Ann M.; Burns, Daniel K.; Lutz, Michael W.; Runyan, Grant; Lai, Eric; Budur, Kumar; et al.
Abstract: Introduction: Dementia is one of the major health threats to our aging society, and Alzheimer's disease (AD) is the leading cause. In Japan, ∼15% of the elderly population has dementia. The apolipoprotein E ( APOE ) genotype and a polymorphism (rs10524523) in the translocase of outer mitochondrial membrane 40 ( TOMM40 ) gene have been associated with the age of onset of AD. However, differences in allele frequencies of these markers in different ethnic populations are not well known. Methods: Whole blood samples were collected from 300 Japanese subjects, and genomic DNA was extracted to determine APOE alleles and TOMM40 rs10524523 genotypes. Results: Our results indicated that the APOE ε3– TOMM40 ′523 short haplotype is less frequent in Japanese subjects than in Caucasians, whereas the APOE ε3– TOMM40 ′523 long and APOE ε3– TOMM40 ′523 very long haplotypes are more frequent in Japanese subjects than in Caucasians. We also showed that the APOE ε4– TOMM40 ′523 short haplotype, which was noted to be frequently observed in African Americans, was also found in the Japanese population, although it is extremely rare in the Caucasian population. Discussion: A biomarker risk assignment algorithm, using a combination of APOE, TOMM40 ′523 genotype, and age, has been developed to assign near‐term risk for developing the onset of mild cognitive impairment due to AD and is being used as an enrichment tool in an ongoing delay‐of‐onset clinical trial. Understanding the characterization of APOE and TOMM40 allele frequencies in the Japanese population is the first step in developing a risk algorithm for AD research and clinical applications for AD prevention in Japan. Highlights: Linkage between the translocase of outer mitochondrial membrane 40 ( TOMM40 ′523) and apolipoprotein E ( APOE ) allele differs depending on the population. The APOE ε3– TOMM40 ′523 short haplotype is less frequent in the Japanese population than in Caucasian ones. The APOE ε3– TOMM40 ′523 long and very long haplotypes are more frequent in the Japanese population than in Caucasian ones.